2017
DOI: 10.2169/internalmedicine.8360-16
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab-resistant TAFRO Syndrome Complicated by Type II Respiratory Failure

Abstract: A 66-year-old man with a several year history of thrombocytopenia, pleural effusion and ascites, anasarca, and organomegaly presented with general fatigue, appetite loss, dyspnea with type II respiratory failure. The precise history of the patient and the re-evaluation of lymph node and bone marrow biopsies conducted by the previous physician indicated TAFRO syndrome. The patient's laboratory data improved for a year with tocilizumab, but then worsened to the point that the patient required artificial ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Fujiki et al reported a case of TAFRO syndrome complicated with severe infection during corticosteroid therapy, which was successfully treated with TCZ alone [17]. However, cases of TCZ-resistant TAFRO syndrome have been reported [15,18]. Clinical experiences of using rituximab, cyclophosphamide, and thalidomide have been reported from Japan [19][20][21] In the present case, as combination treatment with PSL and CsA appeared ineffective even after 5 weeks, and TCZ was considered an alternative immunosuppressant.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Fujiki et al reported a case of TAFRO syndrome complicated with severe infection during corticosteroid therapy, which was successfully treated with TCZ alone [17]. However, cases of TCZ-resistant TAFRO syndrome have been reported [15,18]. Clinical experiences of using rituximab, cyclophosphamide, and thalidomide have been reported from Japan [19][20][21] In the present case, as combination treatment with PSL and CsA appeared ineffective even after 5 weeks, and TCZ was considered an alternative immunosuppressant.…”
Section: Discussionmentioning
confidence: 64%
“…Abbreviations ALP: Alkali phosphatase; CAG: Coronary angiography; CD: Castleman disease; CMV: Cytomegalovirus; CRP: C-reactive protein; CRRT: Continuous renal replacement therapy; CsA: Cyclosporine A; CT: Computed tomography; FDG-PET: 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other cases demonstrating this overlap. Presence of neuropathy is also seen in TAFRO patients while this presentation is mostly seen with POEMS (5). Regardless of different and overlapping presentations, managing TAFRO is another challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of cyclophosphamide may reduce the therapeutic dose of steroids and reduce the adverse effects of steroid (6). Aoki et al reported a case of TAFRO syndrome which did not respond to tocilizumab (5). They suggested that rituximab is a good choice in patients who do not respond to tocilizumab therapy (5).…”
Section: Discussionmentioning
confidence: 99%